Measuring Feed Force in Machining Using a Strain Gage - Salman Al Farisi Siregar; Agus Triono; Mahros Darsin; Santoso Mulyadi (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2021)
Measuring the forces that work during machining has been being concerned by researchers for years. There are three main forces that work in turning: thrust  force, axial force, and radial force. Thus, feeding force measurement is needed in machine manufacturing. This research attempts to develop measurement method through feeding force, using strain gauge sensor. The aim of measurement of feeding force in this research is to find out the influence parameter of machine towards feeding force. The research used experimental method with design experiment Taguchi to know the influence of machine parameters to feeding force in turning process. The measurement tool is strain gauge sensor connected to cutting tool. The workspace is alluminium 6061 with 15 mm in diameter and 150 mm in length. The  parameters for this research are speed rate (140 rpm, 215 rpm, and 330 rpm), feed rate (0,043 mm/r , 0,065 mm/r , and 0,081 mm/r), and depth of cut (0,2 mm, 0,4 mm, and 0,6 mm). The result showed that speed rate is the most significant parameter, with the contribution percentage is 92 %. Speed rate and feed rate parameter have insignificant influence. The contribution percentage of speed rate is 2% while the feed rate has % contribution percentage. The conclusion of the research is that the bigger number of speed rate, the bigger feeding force it will have.